Dimensions of Rational Decision-Making during the Demographic Transition; Aranjuez (Spain) Revisited - David Reher; Glenn Sandström (Historical Life Course Studies)
A set of linked reproductive histories taken from the Spanish town of Aranjuez during the demographic transition is used to address key issues regarding reproductive change and reproductive choice. This paper builds on the existing literature and especially on the findings first shown in Reher & Sanz-Gimeno (2007) and in Van Poppel et al. (2012) where the links between childhood survival and reproductive decision-making were specified. This paper goes beyond the original ones in two  important ways: (a) the sex composition of the surviving sibset is included in the analysis and (b) behavior is modeled by means of event history analysis. In these models, controls for the survival status of the previous child are introduced so as to distinguish between biological factors related to the cessation of breastfeeding and both short term (child replacement) and more long-term reproductive strategies. The results offer convincing proof that couples were continually regulating their fertility in order to achieve reproductive goals both in terms of net fertility and of the sex composition of the resulting sibset. Here results show that both sexes were desired by parents but that lack of surviving males had greater influence on fertility behavior. As expected, controls for the survival status of the previous-born child were important though they did not diminish appreciably the overall effect of the number of surviving offspring. This article offers strong proof for the existence of active decision-making during the demographic transition and applies a method to model these behaviors over the full reproductive history of the couple.